Penerapan Teknik Sinematografi oleh Director of Photography pada Video Feature “Ibu untuk Bumi” Bertema Gaya Hidup Berkelanjutan - Ikhwan Amar Mahesa; Toto Sugito; Andri Yanto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This final project aims to examine how cinematographic techniques are applied by the Director of Photography (DoP) to enhance the delivery of visual messages in the feature video "Ibu untuk Bumi", which highlights the role of mothers in shaping sustainable lifestyle habits within the family. This research employs a qualitative approach using a production study method. The author was directly involved as the DoP, designing the visual concept from pre-production to post-production. The analyzed elements include composition arrangement, camera angle selection, shot type, camera movement, and lighting. Shots such as medium shots and close-ups were used to build emotional closeness between the subject and the audience. The lighting system combined key light, fill light, and back light to create a natural atmosphere that supports the narrative. The results show that consciously designed cinematographic techniques can reinforce the message of a feature video, especially when the visual narrative focuses on everyday life relatable to the audience. This work demonstrates that the DoP plays a vital role in delivering social messages and shaping a reflective and empathetic viewing experience.